The Effectiveness of a Multimedia Educational Program on the Lifestyle and Perception of Patients with Atrial Fibrillation: A Study Protocol - Shirin Madadkar Dehkordi; Zohreh Karimiankakolaki; Parvin Mohammadi; Shirin Mirzaeian (Journal of Social Behavior and Community Health)
Background: Atrial fibrillation is a globally common cardiac dysrhythmia and preventable with education. The study protocol aimed to investigate the effectiveness of a multimedia educational program on the lifestyle and perception of patients with atrial fibrillation. Methods: The present clinical trial protocol will be conducted to investigate the effect of multimedia training on the lifestyle and perception of patients with atrial fibrillation in two phases. The multimedia training (audio, video, image, and animation) was  provided in the form of two 2-hour training sessions per week for patients on the coordinated date and time on a web platform. The patients also received a weekly phone call for one month through which some educational content was covered as a type of training intervention. The second phase included the administration of pre-test and post-test interventions using standard questionnaires by an intervention (who receive training) and a control (without training) group. Conclusion: The present study provides a useful protocol regarding the design of a multimedia educational intervention program on promoting the lifestyle and perception of patients with atrial fibrillation. It can also reduce treatment costs. The strategies of this program can be cost-effective therefore the success of such a program can be effective in improving the health status of atrial fibrillation patients.Registration of this randomized control trial has been completed with the Iranian Registry of Clinical Trials.